Stability and Change in Guale Indian Pottery, A.D. 1300-1702 - Saunders, Rebecca, 1955- (Book collections on Project MUSE., 2000)
Through a comprehensive study of changing pottery attributes, Saunders documents the clash of Spanish and Native American cultures in the 16th-century southeastern United States. By studying the ceramic traditions of the Guale Indians, Rebecca Saunders provides evidence of change in Native American lifeways from prehistory through European contact and the end of the Mission period. The Guale were among the first southeastern groups to come into contact with Spanish and French colonists, and they adapted various strategies in order to ensure their own social survival. T.